Phylogenetic characterization and ochratoxin A - Fumonisin profile of black Aspergillus isolated from grapes in Argentina - Chiotta, María Laura (2011)
Aspergillus section Nigri populations isolated from seven growing regions from Argentina were characterized by sequencing in order to identify species responsible for production of ochratoxin A (OTA) and fumonisins (FBs). Sequences of genes encoding calmodulin, β-tubulin, the second largest subunit of RNA polymerase II and translation elongation factor 1 alpha were analysed. The phylogenetic analysis showed the presence of six lineages: A. carbonarius, A. tubingensis, A. niger, A. japonicus, A. homomorphus and A. foetidus grouped in four major clusters. The molecular tools used allowed the identification for the first time of A. homomorphus from vineyards. OTA production confirmed the importance of A. carbonarius as the main ochratoxigenic species isolated and, to a variable degree, of A. niger and A. tubingensis, which were by far the most commonly occurring species on grapes in Argentina. The only strains able to produce OTA and fumonisins (B2-B4) belong to the A. niger cluster.